Political Return of Metaphysics - Jokubaitis, Alvydas (Politologija, 2025)
The aim of the paper is to prove that metaphysics which was criticized by Immanuel Kant in his philosophy returned by way of politics. His philosophy of history reintroduces what he rejected as faulty metaphysics. What Kant speaks about history can be applied to politics. Metaphysics, which was expelled in the Critique of Pure Reason and provided with a novel explanation in the Critique of Practical Reason, returned in the Critique of Judgement under new guises and with old contradictions. By rejecting metaphysical speculations Kant opened the way for political speculations.
Keywords: Kant; metaphisics; politics; philosophy of history; aesthetics